A first case of isolation of Kerstersia gyiorum from urinary tract. Issue 4 (April 2016) - Ogawa, Yoshihiko; Lee, Sang-Tae; Kasahara, Kei; Koizumi, Akira; Chihara, Yoshitomo; Nakano, Ryuichi; Yano, Hisakazu; Mikasa, Keiichi
Abstract: An 82-year-old man with percutaneous nephrostomy presented to our Hospital with dysuria for one day. The patient's percutaneous nephrostomy tube was exchanged, with about 20 mL of creamy purulent urine being collected. Direct smear of the urine specimen showed polymorphonuclear leukocytes and small Gram-negative bacilli, some of which had undergone phagocytosis. This organism was identified as Kerstersia gyiorum using 16S ribosomal RNA gene analysis. He was successfully recovered with exchange of his percutaneous nephrostomy tube and fluoroquinolone internal use treatment. This is the first case report of urinary tract infection due to K. gyiorum .